Redox Coupling of Arylmagnesium Reagents with Gem-Dichloroalkanes Enables C(sp2)−C(sp3)/C(sp3)−C(sp3) Bond Formations - Chen, Rong; Yu, Wenhua; Wei, Shaopeng; Ouyang, Feng; Yu, Guipeng; Wei, Baosheng (Synthesis, 2025)
The oxidative homocoupling of organomagnesium reagents has been well studied, but the sacrificial oxidants used in these reactions are usually not incorporated into the coupling products. Herein, we report a chromium- or manganese-catalyzed coupling reaction of arylmagnesium reagents with gem-dichloroalkanes (RR′CCl2), in which RR′CCl2 serves as both oxidant and coupling reagent. This catalytic redox coupling reaction enables the convenient synthesis of various functionalized dibenzyl derivatives via successive C(sp2)−C(sp3)/C(sp3)−C(sp3) bond formations. A radical-involved mechanism is proposed and experimentally evidenced.
Keywords: Coupling; Organomagnesium reagent; Chromium; Manganese; gem-Dichloroalkane; Dibenzyl; Carbon–carbon bond formation